2014
DOI: 10.1038/nprot.2014.157
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing in rice and wheat using the CRISPR/Cas system

Abstract: Targeted genome editing nucleases, such as zinc-finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs), are powerful tools for understanding gene function and for developing valuable new traits in plants. The clustered regularly interspersed short palindromic repeats (CRISPR)/Cas system has recently emerged as an alternative nuclease-based method for efficient and versatile genome engineering. In this system, only the 20-nt targeting sequence within the single-guide RNA (sgRNA) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
465
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 647 publications
(475 citation statements)
references
References 54 publications
5
465
0
5
Order By: Relevance
“…The presence of these sites is a parameter that can be taken into account when selecting the sgRNAs. Knock-in events presenting disrupted restriction sites will resist to the digestion and be available for a much more efficient and detectable amplification [11]. Furthermore, positive and/or negative selection markers, as well as a high selection pressure for gene modifications during the regeneration process (when the desired phenotype is amenable to it), can be used to increase the probability to see knock-in events [27][28][29].…”
Section: Detection Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of these sites is a parameter that can be taken into account when selecting the sgRNAs. Knock-in events presenting disrupted restriction sites will resist to the digestion and be available for a much more efficient and detectable amplification [11]. Furthermore, positive and/or negative selection markers, as well as a high selection pressure for gene modifications during the regeneration process (when the desired phenotype is amenable to it), can be used to increase the probability to see knock-in events [27][28][29].…”
Section: Detection Proceduresmentioning
confidence: 99%
“…As for free DNA fragments, they varied from 72 to 476 bp including homology arms, of even length or not, of 46 to 146 bp [6,11,67,69]. Rare are the situations (involving the same protocol, target and plant species) allowing to compare the impact of the nature and length of the homologies on knock-in efficiency.…”
Section: With Homology To the Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…In this system, only 20-nucleotide target sequences (or even one nucleotide) form the target gene with a desirable sequence of gene needs to be altered (Fig 3). Shan et al (2014) suggested the (CRISPR)/Cas9 as an appealing system due to its simplicity. They described a stepwise protocol for the selection of target sites, design, construction, verification and use of single guide RNA (sgRNAs) for sequence-specific mutagenesis in target genes of rice and wheat.…”
Section: Gene Editing Using Crispr/cas9 To Design and Produce Novel Mmentioning
confidence: 99%